Helyi tömegközlekedés vizsgálata egy közép-kelet-európai vidéki városban - Gál, József (Közép-Európai Közlemények, 2010)
The main goal is to learn more about local public transport of the town Hodmezovasarhely. I am looking for the answer about planning optimum of costs and transport service. There was a passenger counting inside running buses at each bus stops and twice on workdays, furthermore twice on weekends. I present results on diagrams from different aspects line by line. I offer some new schedule construction, because in the early morning and late night less than 10 passengers can be counted in some buses. Optimize costs and schedule are very important either passengers or government and local government. It determines fare. Transport companies often decide reduce number of buses and lines, but it makes big troubles for inhabitants. Between demands and real use you can find gap. One of the main questions is how to organize schedule to be acceptable for everybody.